Induced Pluripotent Stem Cells for Inherited Optic Neuropathies—Disease Modeling and Therapeutic Development. Issue 1 (30th March 2022) - Harvey, Joshua Paul; Sladen, Paul Edward; Yu-Wai-Man, Patrick; Cheetham, Michael E.
Abstract : Background: Inherited optic neuropathies (IONs) cause progressive irreversible visual loss in children and young adults. There are limited disease-modifying treatments, and most patients progress to become severely visually impaired, fulfilling the legal criteria for blind registration. The seminal discovery of the technique for reprogramming somatic nondividing cells into induced pluripotent stem cells (iPSCs) has opened several exciting opportunities in the field of ION research and treatment. Evidence Acquisition: A systematic review of the literature was conducted with PubMed using the following search terms: autosomal dominant optic atrophy, ADOA, dominant optic atrophy, DOA, Leber hereditary optic neuropathy, LHON, optic atrophy, induced pluripotent stem cell, iPSC, iPSC derived, iPS, stem cell, retinal ganglion cell, and RGC. Clinical trials were identified on the ClinicalTrials.gov website. Results: This review article is focused on disease modeling and the therapeutic strategies being explored with iPSC technologies for the 2 most common IONs, namely, dominant optic atrophy and Leber hereditary optic neuropathy. The rationale and translational advances for cell-based and gene-based therapies are explored, as well as opportunities for neuroprotection and drug screening. Conclusions: iPSCs offer an elegant, patient-focused solution to the investigation of the genetic defects and disease mechanisms underpinning IONs. Furthermore, this group of disorders is uniquely amenable to both the disease modeling capability and the therapeutic potential that iPSCs offer. This fast-moving area will remain at the forefront of both basic and translational ION research in the coming years, with the potential to accelerate the development of effective therapies for patients affected with these blinding diseases.